Family Support Towards the Practice of Providing Complementary Breast Milk (PPC-BM) to Infants Aged 6-12 Months - Jafri, Yendrizal; Kasrin, Rinawati; Impian, Rara Raih; Sari, Lidya Maya (REAL in Nursing Journal, 2025)
Background: Practice Of Providing Complementary Breast Milk (PPC-BM) plays an important role in supporting the growth and development of infants aged 6-12 months. WHO and the Indonesian Ministry of Health recommend providing PPC-BM that is timely, nutritious, safe, and meets standards. However, many mothers still face obstacles in providing optimal PPC-BM, especially due to lack of family support. Family support, especially from husbands, grandmothers, and other family members, greatly influences the success of PPC-BM practices. Objective: This study aims to analyze the relationship between family support and complementary feeding practices in infants aged 6-12 months in the Gulai Bancah Health Center working area, Bukittinggi City. Method: This study used a cross-sectional design with a quantitative approach. Samples were taken using cluster random sampling technique, with a total of 222 mothers with infants aged 6-12 months as respondents. Data were collected using a structured questionnaire that measured family support (emotional, instrumental, information, and assessment) and complementary feeding practices. Data analysis was performed using the Chi-Square test to see the relationship between variables. Conclusion: the results of the study showed that most mothers received family support in the good (54.1%), sufficient (36.0%), and less (9.9%) categories. The practice of providing complementary feeding by mothers was also mostly in the good (58.6%), sufficient (31.5%), and less (9.9%) categories. Statistical tests showed a significant relationship between family support and complementary feeding practices (p-value <0.05). Mothers who receive good family support are more likely to provide appropriate complementary feeding according to WHO and Indonesian Ministry of Health standards. Family support plays a crucial role in determining the success of complementary feeding practices that meet health standards. Suggestion: a family-based education strategy is needed through counseling programs, training of integrated health post cadres, and community-based interventions to increase family involvement in complementary feeding practices.Keywords: Family support, complementary feeding, provision practices, infants aged 6-12 months, pediatric nursing.